Association of Circulating Cathepsin B Levels With Blood Pressure and Aortic Dilation - Chai, Tianci; Tian, Mengyue; Yang, Xiaojie; Qiu, Zhihuang; Lin, Xinjian; Chen, Liangwan (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is a key risk factor for spontaneous coronary artery dissection (SCAD) and aortic dilation. Circulating proteins play key roles in a range of biological processes and represent a major source of druggable targets. The aim of this study was to identify circulating proteins that were associated with blood pressure (BP), SCAD and aortic dilation. We identified shared genetic variants of BP and SCAD in genome-wide association studies, searched for circulating protein affected by these variants and examined the association of circulating protein levels with BP, aortic aneurysm and dissection (AAD) and aortic diameters by integrating data from circulating protein quantitative trait loci (pQTL) studies and genome wide association study (GWAS) in individuals from the UK Biobank using two-sample Mendelian randomization analysis methods. SNPs in JAG1, ERI1, ULK4, THSD4, CMIP, COL4A2, FBN1, FAM76B, FGGY, NUS1 and HNF4G, which were related to extracellular matrix components, were associated with both BP and SCAD. We found 49 significant pQTL signals among these SNPs. The regulated proteins were encoded by MMP10, IL6R, FIGF, MMP1, CTSB, IGHG1, DSG2, TTC17, RETN, POMC, SCARF2, RELT and GALNT16, which were enriched in biological processes such as collagen metabolic process and multicellular organism metabolic process. Causal associations between BP and AAD and aortic diameters were detected. Significant associations between circulating levels of cathepsin B, a well-known prorenin processing enzyme, and BP and aortic diameters were identified by using several Mendelian randomization analysis methods and were validated by independent data. Conclusion: The present study identified the association between circulating cathepsin B and BP and aortic diameters. The findings indicated that BP-associated genetic variants may influence aortic dilation risk by circulating proteins that regulate BP.